ANALISIS PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MEDIA KANTONG KATA KELAS V SD NEGERI GAJAH MUNGKUR 04 SEMARANG - Laeli Novi Rahmalia; Kartinah; Siti Munfarichah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning media are strategies or concepts that can be used to develop curriculum (long-term learning plans), prepare learning materials, and guide classroom teaching. This research aims to evaluate the use of word bags as a learning medium for class V Indonesian language learning at SD Negeri Gajahmungkur 04. The method used is a qualitative method. Qualitative methods are a type of research method that uses descriptions of all activities, objects, processes and research subjects. The information produced is a general description in the form of a text narrative, which explains the overall data that has been collected. Data collection techniques use interviews and documentation. The results of the research state that teachers still use lecture-style teaching methods so that learning still seems boring, so there is a need for innovation in learning media to increase enthusiasm for learning and make students' learning experiences exciting and interesting. The word bag media aims to sharpen students' knowledge of Indonesian language material, namely idioms. With the hope of improving Indonesian language learning outcomes through this media. In this research, it turns out that SD Negeri Gajahmungkur 04 is equipped with adequate facilities to utilize and increase the use of learning media. such as projectors, pictures/knowledge pillars and other facilities available. However, these facilities have not been used optimally due to time constraints in the learning process.